2022
DOI: 10.1111/cid.13113
|View full text |Cite
|
Sign up to set email alerts
|

One‐stage versus two‐stage technique using two splinted extra‐short implants: A multicentric split‐mouth study with a one‐year follow‐up

Abstract: Objective: To compare the clinical outcomes of extra-short implants (≤6.5 mm) inserted with one-stage versus two-stage technique in adjacent sites of the upper or lower jaw. Materials and Methods:In this split-mouth multicenter study, implants were randomly divided into two groups according to the healing phase: two-stage and onestage technique. Primary outcome measures were implant survival, implant success, and prosthodontic complications. Secondary outcome measurements were: implant stability quotient (ISQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The results observed in the present study regarding implant survival rate and MBL of posterior implant supporting multi-unit fixed prosthesis (ISMFP) are in agreement with the data described in the literature with similar observational periods and different implants and techniques. Menini et al [34] reported the outcome of 38 ISMFP placed either with one-stage or two-stage technique. The authors findings showed a survival and success rate of 100% and a MBL of 0.46 ± 0.41 (two-stage) and 0.45 ± 0.38 (one-stage) mm after a 1 year observational period.…”
Section: Discussionmentioning
confidence: 99%
“…The results observed in the present study regarding implant survival rate and MBL of posterior implant supporting multi-unit fixed prosthesis (ISMFP) are in agreement with the data described in the literature with similar observational periods and different implants and techniques. Menini et al [34] reported the outcome of 38 ISMFP placed either with one-stage or two-stage technique. The authors findings showed a survival and success rate of 100% and a MBL of 0.46 ± 0.41 (two-stage) and 0.45 ± 0.38 (one-stage) mm after a 1 year observational period.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the angulated abutments introduced the possibility of tilting the distal implants to avoid the anatomic boundaries (alveolar nerve and maxillary sinus). However, these surgical procedures can result in prolonged treatment times, high costs, and morbidity for the patient [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that the first-year MBL after implant placement is an important factor in the success or failure of implant treatment [ 8 ]. The amount of MBL is influenced by patient-related factors such as the patient’s history of periodontitis, smoking status, and plaque control ability, as well as implant-related factors such as implant connection and geometric configuration [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%